Determination of residual monomers in poly(lactide-co-ε-caprolactone) using gas chromatography - Lidong Feng; Sheng Xiang; Yanlong Liu; Xinchao Bian; Gao Li; Xuesi Chen (Polymer Testing, 2021)
An analytical method was developed to quantitatively determine residual monomers, namely, lactide (LA) and ε-caprolactone (CL), in poly(lactide-co-ε-caprolactone) (PLCL) using an internal-standard method of gas chromatography (GC). PLCL and diphenyl ether (DPE) as an internal standard were initially dissolved in dichloromethane (DCM), and then PLCL was precipitated in cyclohexane. The residual LA and CL monomers in PLCL, as well as DPE, were extracted into cyclohexane from the polymer solution. The resulting solution was directly injected into a GC system. This method was practical for measuring the residual LA and CL contents in PLCL. The relative standard deviation (RSD) (n = 5) denoting the repeatability of this method was less than 5.6% and 4.3% for the LA and CL measurements, respectively, indicating that the method was sufficiently precise. The recovery rate of standard addition was 96.5%–101.5% and 98.4%–104.2% for the determination of LA and CL in PLCL, respectively. The RSD of the recovery of standard addition (n = 5) was not more than 2.0%, indicating that the method was sufficiently accurate.